PENGARUH PENGGUNAAN PEMBELAJARAN ONLINE MELALUI MEDIA APLIKASI ASSEMBRL EDU TERHADAP HASIL BELAJAR SISWA MTs AL ISHLAH MAYANG JEMBER - Muhammad Ilyas; Elga Yanuardianto; Talmizan Al Maghrobi (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
The development of technology in the modern era is very rapid and sophisticated. This development covers various aspects/fields of human life. Likewise, in the world of education, it has a huge influence, especially in student learning activities,However, the use of technology or pedagogy tools is very minimal, because many teachers and students still do not know about the application media, so it is a pedagogy tool. After looking at the problem above then learnonline via application mediaassembrl edu It is hoped that the bus will improve student learning outcomes. The aim of this research is to obtain empirical data and valid and reliable facts aboutis the influence of the use of learningonline via application mediaAssembrl Edu on the learning outcomes of students in the subject of moral aqidah material on bad morals in class VII at MTs Al Ishlah Mayang for the 2022-2023 academic year. With a quantitative research approach, and using data collection techniquesPree Test Post Test, observation, documentation and interviews, as well as using the entire sample from the existing population, namely 20 respondents. using statistical analysis, namely simple linear regression analysis using SPSS Version 2.6. The results of the research state that there is a strong influence relationship of 93.2% between the influence of the use of learningOnline via application mediaAssembrl Edu on student learning outcomes with a very strong correlation of 0.965. This shows that the better the use of educational assembly media by students, the better the student's learning outcomes will be.